Strawberry Notch 1 acts as a transcriptional regulator driving oncogenic programs in liver carcinogenesis - Fritzsche, Sarah; Sugiyanto, Raisatun Nisa; Gür, Kira; Krumme, Alina; Le Marois, Maxime; Fraas, Angelika; Inal, Aslihan; Huerta, Mario; Henriques, Vanessa; Eiteneuer, Eva; Albrecht, Thomas; Charbel, Alphonse; et al. (Advanced science, 2026)
Aberrant Notch signaling has been identified as a key driver of cancer development. Genetic studies in Drosophila showed that the knockout of strawberry notch (sno) mimics the loss of notch. Here, we found that Strawberry Notch 1 (SBNO1) is upregulated in several cancer entities and elucidated the role of SBNO1 in liver cancer development. In hepatocellular carcinoma (HCC) and cholangiocarcinoma (CCA), SBNO1 protein was significantly increased and localized to the nucleus suggesting its involvement in gene regulation. SBNO1-inhibition reduced cell viability, colony formation and migration and induced distinct expression patterns in HCC and CCA cell lines. However, BioID revealed that SBNO1 similarly modulates gene regulation in HCC and CCA by binding to general transcription factors TAF4 and TAF3. Deletion of Sbno1 in murine liver cancer cells Hep55.1C reduced tumor growth in vivo. In addition, inhibition of Sbno1 significantly reduced liver tumor development in three different mouse models of HCC and CCA. Furthermore, Sbno1-deletion reduced biliary differentiation and angiogenesis in the tumor margin, underscoring the necessity of Sbno1 in Notch-driven CCA formation. Thus, we identified SBNO1 as a transcriptional regulator required for liver cancer development and progression.